(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Nowadays, manufacturing firms are in the position to redefine and redesign their manufacturing systems in order to meet the competitive demands raised by market challenges. The manufacturing systems exhibited a key transition from mass manufacturing to lean manufacturing. The Comparative aspects of lean production with that of mass production is presented as follows The focus of lean production is customer whereas mass production focuses on product. Lean production is characterized with synchronized flow and pulls whereas mass production is based on batch and queue operations. The overall aim of lean Production is to eliminate waste and add value whereas mass production focuses on cost reduction and efficiency improvement. Lean production focus on worker driven continuous improvement whereas mass production focuses on expert driven continuous improvement. Lean system is flexible and adaptable whereas mass system works on economies of scale. Quality is an inbuilt function in lean system. The features of lean system include waste elimination limited flexibility to accommodate product complexities non-reconfigurable products and the system not suitable for turbulent market conditions.